Employing the RE-AIM Framework to Evaluate Multisport Service Organization Initiatives. Issue 2 (29th April 2021) - Lawrason, Sarah; Turnnidge, Jennifer; Tomasone, Jennifer; Allan, Veronica; Côté, Jean; Dawson, Karri; Martin, Luc J.
Abstract: The evaluation of Multisport Service Organization (MSO) initiatives can result in a greater understanding of factors related to their success. The RE-AIM framework is an evidence-informed framework for comprehensive evaluations but has not been employed in MSO contexts. The purpose of this study was to develop a template of operationalized RE-AIM indicators for MSO initiatives and to provide a case-study of its application with an existing initiative – True Sport. This template can enable MSO initiatives to leverage existing data for hierarchical and pragmatic evaluations and is generalizable for other sport contexts. Recommendations are advanced for practitioners undertaking sport program evaluations.